Altitude Training, Performance, and Physiological Responses to Exercise (2005)
Athletes and coaches often include altitude training as part of their seasonal plan because of the beneficial effects it can have on performance. The physiological changes that occur as a result of altitude training can have positive effects on both endurance and sprint performance. However, the extent of these effects may depend on the individual swimmer and how their body reacts to altitude. Most research on altitude training has been performed using the live high/train low method, which allows the athlete to train at sea-level intensities, while still obtaining the potential benefits of living at altitude (2,500-3,000m).